International Workshop on Variable Structure Systems, 2006. VSS'06.
DOI: 10.1109/vss.2006.1644488
|View full text |Cite
|
Sign up to set email alerts
|

On the Discrete-Time Integral Sliding Mode Control

Abstract: A new discrete-time integral sliding mode control (DISMC) scheme is proposed for sampled-data systems. The new control scheme is characterized by a discrete-time integral switching surface which inherits the desired properties of the continuous-time integral switching surface, such as full order sliding manifold with eigenvalue assignment, and elimination of the reaching phase. In particular, comparing with existing discrete-time sliding mode control, the new scheme is able to achieve more precise tracking per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(103 citation statements)
references
References 7 publications
0
103
0
Order By: Relevance
“…Proof of Lemma 1: See [14,15]. Then, we offer the following design steps, and each step is developed based on the insights of classical control theory.…”
Section: Current-output Observer-based Lqdt For Nmp Discrete-time Sysmentioning
confidence: 99%
“…Proof of Lemma 1: See [14,15]. Then, we offer the following design steps, and each step is developed based on the insights of classical control theory.…”
Section: Current-output Observer-based Lqdt For Nmp Discrete-time Sysmentioning
confidence: 99%
“…kT c y kT    cx cx cx (15) Vector c in relation (15) is selected to ensure a finite time response of the discrete system [43], which means it must satisfy …”
Section: Control Strategymentioning
confidence: 99%
“…[14]. Afterwards, an integral sliding mode control strategy has also been proposed in order to eliminate the reaching phase in discrete time sliding mode control [15]. An exhaustive review of the discrete time sliding mode control literature can be found in paper [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research progress of chattering suppression mainly has two directions. One is to introduce integrator in SMC so that discontinuous function after integral becomes continuous [6]- [8]. The other is to increase the order of SMC [9], based on which super twisting algorithm is proposed and combined with adaptive change of control gain [10].…”
Section: Introductionmentioning
confidence: 99%